Physicochemical Characterization of Poly(L-lactic acid) Microspheres Bearing Bromhexine Hydrochloride - OZLEN SAHIN, NEFISE; ARSLAN, HAKAN (Asian Journal of Chemistry, 2010)
This work embodies the details of a project on characterization of controlled-release dosage form of bromhexine hydrochloride to prevent gastric irritation. The sustained release formulations of bromhexine hydrochloride were prepared using poly(L-lactic acid) with the method of emulsion/ solvent evaporation technique. The physicochemical characterizations of microspheres were investigated by X-ray powder diffraction and DSC analysis techniques. The DSC thermograms of drug loaded microspheres were different from bromhexine hydrochloride. Based on the data, it was evident that a crystalline fraction of the drug exists in microspheres when drug:polymer ratio was 1:1. X-ray diffraction patterns indicate a possible interference between the drug and the polymer. In conclusion, the sustained release formulations dosage form of bromhexine hydrochloride prepared with 1:1 drug:polymer ratio is the best formulation.